Electromyography-Informed Estimates of Joint Contact Forces Within the Lower Back and Knee Joints During a Diverse Set of Industry-Relevant Manual Lifting Tasks. - Davenport, Felicia R.; Leestma, Jennifer K.; Staten, Adriana; Bhakta, Krishan; Fernandez, Joshua; Mazumdar, Anirban; Young, Aaron J.; Sawicki, Gregory S. (Journal of Applied Biomechanics, 2025)
Repetitive manual labor tasks involving twisting, bending, and lifting commonly lead to lower back and knee injuries in the workplace. To identify tasks with high injury risk, we recruited N = 9 participants to perform industry-relevant, 2-handed lifts with a 11-kg weight. These included symmetrical/asymmetrical, ascending/descending lifts that varied in start-to-end heights (knee-to-waist and waist-to-shoulder). We used a data-driven musculoskeletal model that combined force and motion data with a muscle activation-informed solver (OpenSim, CEINMS) to estimate 3-dimensional internal joint contact forces (JCFs) in the lower back (L5/S1) and knee. Symmetrical lifting resulted in larger peak JCFs than asymmetrical lifting in both the L5/S1 (+20.2% normal [P <.01], +20.3% shear [P =.001], +20.6% total [P <.01]) and the knee (+39.2% shear [P =.001]), and there were no differences in peak JCFs between ascending versus descending motions. Below-the-waist lifting generated significantly greater JCFs in the L5/S1 and knee than above-the-waist lifts (P <.01). We found a positive correlation between knee and L5/S1 peak total JCFs (R2 =.60, P <.01) across the task space, suggesting motor coordination that favors sharing of load distribution across the trunk and legs during lifting.